A STUDY ON DIGITAL CITIZENSHIP: PRESCHOOL TEACHER CANDIDATES VS. COMPUTER EDUCATION AND INSTRUCTIONAL TECHNOLOGY TEACHER CANDIDATES - Elmali, Filiz; Tekin, Ahmet; Polat, Ebru (Anadolu Univ, 2020)
The main goal of this study is to determine the digital citizenship perceptions and digital citizenship levels of preschool teacher candidates in terms of digital rights and responsibilities, digital security and digital law by comparing them with Computer and Instructional Technologies teacher candidates' perception. To this end, we worked with 80 teacher candidates in total. Both qualitative and quantitative research methods were employed. To identify participants' digital citizenship levels, a questionnaire was administered. Also, semi-structured interviews were conducted to understand their digital citizenship perceptions. The results showed that participants' digital citizenship levels were above average and their digital citizenship perceptions supported this result. In addition, their responses related to digital security, digital rights and responsibilities, and digital law were parallel to their definitions in the literature and they connected them with digital communication and ethics. However, teacher candidates' misconceptions in terms of digital rights and responsibilities and digital security were observed.
Keywords: Teacher candidates; technology; digital citizenship; digital citizenship perceptions